Development of Murine Hepatic NK Cells during Ontogeny: Comparison with Spleen NK Cells - Xian Wu; Yongyan Chen; Haiming Wei; Rui Sun; Zhigang Tian (Clinical and Developmental Immunology)
The phenotype of developing liver NK cells (CD3−NK1.1+) was investigated during mouse ontogeny comparing with spleen NK cells. The highest percentage of hepatic CD27−CD11b− NK cells occurred at the fetal stage. After birth, the percentage of CD27−CD11b−NK cells in both the liver and spleen gradually decreased to their lowest level at 6 weeks. More CD27+CD11b−NK cells were detected in the liver than that in spleen from week 1 to 6. Expression of NKG2A on liver NK cells was decreased but still much higher than that of spleen NK cells after 1 week. The NKG2D expression on liver NK cells increased to its highest level and was significantly higher than on spleen NK cells till 4 weeks. During mouse ontogeny, weaker expression of NKp46 and CD2 and stronger expression of CD69, CD11c, 2B4, and CD73 were observed on liver NK cells. Furthermore, neonatal liver NK cells express higher IFN-γ and perforin than adult .These results suggest that the maturation process of NK cells is unique in the livers, and liver microenvironments might play critical roles to keep NK cells in an immature status.